钱钟书《围城》的人性困境: Human Nature Dilemma of Zhongshu Qian’s Fortress Besieged - Yap Beng Hui, Teoh Hooi See 叶明慧，张惠思 (Journal of Sinological Studies 漢學研究學刊, 2024)
钱钟书(1910年—1998年)的《围城》反映了人类的“无毛两足动物的基本根性”，象征一种人性的困境。这是一种人性科学的表达方式，蕴含人性心理学与哲学的理性成分。钱钟书通过当中人物尤其是主人公方鸿渐的各种人事应对与其潜意识，暴露出他如何因心理上的自卑情结与不安全感，从而陷入欲望、现实与良心的无尽纠结与彷徨当中。其实，这是人们普遍具有的心理常态，更是一般人类普遍面对的一种人性困境。本文将征引弗洛伊德的自我心理学与阿德勒的个体心理学理论，探讨钱钟书对《围城》主人公方鸿渐的心理揭示，通过对其自卑情结的分析来挖掘其心灵对安全感的诉求，进而省思人性的困境。 Zhongshu Qian (1910–1998) in his novel Fortress Besieged (1910–1998) reflects what he describes as “Basic nature of hairless, two-legged animals”, symbolizing a fundamental dilemma of human nature. This represents a scientific expression of human nature, imbued with rational elements of psychological and philosophical insight. Through the characters—especially the protagonist Fang Hongjian—and his various responses to social situations, along with his subconscious impulses, Zhongshu Qian reveals how Fang becomes entangled in an endless struggle between desire, reality, and conscience, driven by a deep-seated inferiority complex and a pervasive sense of insecurity. In fact, this psychological state is common among individuals and reflects a universal human predicament. Drawing on Freud’s ego psychology and Adler’s individual psychology, this paper explores Zhongshu Qian’s psychological portrayal of Fang Hongjian in Fortress Besieged, analyzing his inferiority complex in order to uncover his soul’s longing for security, and ultimately to reflect on the broader dilemma of human nature.